Use of global experience in renting residential property to solve the housing problem in Ukraine - Zeltser, Y.R. (Ways to Improve Construction Efficiency, 2023)
Today, the state has ceased to be a subject of active housing policy. The amounts of funds allocated by it for housing construction and financing of state housing programs are extremely insufficient. Thus, according to the new state housing program eOselya in Diya, the operator of which is PJSC UKRFINZHYTLO, in 2022-2023, the state issued only 1,017 loans to Ukrainians in the amount of 1 billion 339.4 million UAH. The high level of commercialization of the housing construction sector, combined with insufficient amounts of state funding for housing construction, as well as the state’s de facto refusal to regulate the residential real estate market, lead to the fact that the level of housing affordability for Ukrainian citizens is extremely low. This inhibits the development of the construction industry, reduces the supply of housing on the real estate market, and contributes to the further deepening of the acute housing crisis in Ukraine. Since the beginning of hostilities, the problem of providing citizens with housing has become even more urgent. Damages from the destruction of the housing stock are estimated at 54.4 billion. For more than a year of war, a total of almost 158,000 residential buildings were damaged or destroyed. It is clear that state housing programs in Ukraine need further development and reform. For this, in particular, it is necessary to develop the rental housing sector, which is an important element of the housing market in most countries of the world. Currently, construction of rental housing is practically non-existent in Ukraine, while in many other countries such construction is an important component of state housing policy. Solving the tasks presented in this article will make a significant contribution to the successful reform of state housing programs in Ukraine and will allow the state to create a separate direction for solving this problem by introducing a mechanism for providing citizens with housing on rental terms.